A robust fluorescent probe for detection of telomerase activity in vitro and imaging in living cells via telomerase-triggering primer extension to desorb DNA from graphene oxide. Issue 15 (3rd July 2018) - Gao, Fenglei; Yao, Yao; Wu, Jing; Cui, Lin; Zhang, Yu; Geng, Deqin; Tang, Daoquan; Yu, Yanyan
Abstract : A novel strategy for telomerase imaging was developed based on telomerase-triggering primer extension to desorb fluorophore labeled DNA from graphene oxide. Abstract : We have developed a robust nanoprobe, named graphene oxide (GO) loaded fluorophore labeled DNA oligonucleotide probe (GO nanoprobe), for the detection of telomerase activity and demonstrated its application for imaging of telomerase in living cells. Two DNA oligonucleotides were used in the sensing system including a FAM-DNA template probe and a short TS primer. Upon the addition of telomerase and dNTPs, the TS primer produced a telomeric repeated sequence at the 3′ end, which was just complementary to the single strand tail of FAM-DNA absorbed on the GO surface; the resulting DNA duplex chain could easily detach from the GO, due to the weak binding force between long dsDNA and GO, which led to the separation of the FAM from the GO surface and brought about an amplified fluorescence emission. The fluorescence signal intensity depended on the amount of telomerase, leading to a novel strategy for detecting and in situ imaging of the cytoplasmic telomerase activity. The GO nanoprobe provided a one-step incubation technique for monitoring the telomerase activity in living cells. The proposed approach also distinguished normal cells from cancer cells and monitored the change in telomerase activity in response to a telomerase inhibitor, demonstrating its potential in clinical diagnostic and therapeutic monitoring.